2018
DOI: 10.1016/j.drugalcdep.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use during alcohol treatment is associated with alcohol-related problems one-year post-treatment

Abstract: Background: Prior research shows that cannabis use during treatment for Alcohol Use Disorders (AUD) is related to fewer abstinent days from alcohol, although only among those who use cannabis 1–2x/month. Here we extend prior research by assessing the relationship between the frequency of cannabis use during AUD treatment and post-treatment alcohol-related consequences. Methods: Data come from the Combined Pharmacotherapies and Behavioral Interventions (COMBINE) Study, a large US randomized control trial of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2122
2122

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Notably, in contrast to some prior work suggesting a detrimental effect of cannabis on drinking outcomes [2,27,36], both the infrequent and frequent cannabis use group in this study consumed 28% fewer drinks on days when cannabis was used. Conversely, one recent study suggested that, among individuals engaged in alcohol treatment who also use cannabis, those who used cannabis once or twice per month had fewer alcohol-abstinent days at the end of treatment, whereas for those who used more frequently, cannabis was not associated with increased alcohol use during treatment compared to cannabis abstainers [10].…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, in contrast to some prior work suggesting a detrimental effect of cannabis on drinking outcomes [2,27,36], both the infrequent and frequent cannabis use group in this study consumed 28% fewer drinks on days when cannabis was used. Conversely, one recent study suggested that, among individuals engaged in alcohol treatment who also use cannabis, those who used cannabis once or twice per month had fewer alcohol-abstinent days at the end of treatment, whereas for those who used more frequently, cannabis was not associated with increased alcohol use during treatment compared to cannabis abstainers [10].…”
Section: Discussioncontrasting
confidence: 99%
“… 17 Secondary analyses of the Combined Pharmacotherapies and Behavioral Interventions (COMBINE) Study data were conducted to examine the effects of cannabis use on drinking and on alcohol-related consequences 1 year posttreatment. 18 , 19 In support of the complementary hypothesis, any cannabis use relative to nonuse during treatment was associated with fewer abstinent days at the end of treatment. However, a nuanced association was uncovered such that those who used cannabis once or twice per month had significantly fewer alcohol-abstinent days after treatment.…”
Section: Resultsmentioning
confidence: 84%
“…More frequent cannabis use during AUD treatment in Project COMBINE also was associated with increased alcohol-related physical consequences 1 year after treatment. 19 Similarly, another secondary analysis of the U.S. National Alcohol Survey data from the general population subsamples of individuals previously treated for AUD showed that mid-level use (use of cannabis more than monthly but less than weekly) was associated with drinking more frequently, having more drinks per drinking occasion, and being more likely to experience alcohol-related harms relative to abstainers. 20 Together, these studies suggest that cannabis use may be complementary to alcohol use among individuals who have received treatment for AUD, although perhaps only at certain frequencies of use.…”
Section: Resultsmentioning
confidence: 99%
“…This sex difference may be related to evidence that comorbidity is more common among women than men (Kessler et al, 1997), which may impact recovery, or biologic differences between men and women in the neurocircuits involved in addiction that impact recovery (Arain et al, 2013). Future research should assess the extent to which women may be substituting marijuana for alcohol to reduce drinking and aid in recovery (Subbaraman, 2014), even though research has not supported the effectiveness of this substitution (Subbaraman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we need to understand whether marijuana use impacts not only the potential progression of problematic drinking, but also whether it effects the remission of alcohol problems. Subbaraman et al (2018) offer evidence that marijuana use may impede recovery from alcohol problems among those in a treatment program. Pacula et al (2008) found that comorbid use of marijuana and alcohol was associated with more costly and longer alcohol use disorder treatment.…”
Section: Introduction 11 Alcohol and Marijuana Interrelationshipsmentioning
confidence: 99%